Introducing Literature Critically and Creatively to Bangladeshi University Students - Farida, Nevin; Sinha, Begum Shahnaz (Journal of NELTA, 2014)
In the National Curriculum for the Secondary and Higher Secondary levels in Bangladesh, there is hardly any focus on English literature in the English syllabus. Students who enter the English Department of Dhaka University face great difficulties in tackling literature. This paper aims to show how we meet the needs of our learners. We draw upon the techniques of close reading and stylistics to develop students’ critical and creative abilities in order to respond to literature. This paper will also share some of the materials and activities used in the classroom by the teachers. DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10329 Journal of NELTA, Vol 18 No. 1-2, December 2013; 41-52